Sosialisasi Rempah Bahan Bumbu Rendang yang Terstandarisasi untuk Pemenuhan Kebutuhan di Sentra Rendang Kota Padang - Novri Nelly; Eka Candra Lina; Ardi Ardi; Indra Dwipa; Prima Fithri; Berri Brilliant Albar; Muhammad Makky; Astri Harnov Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Spices or seasonings are something that determines the taste of Rendang. Standardization of spices as seasoning ingredients is needed to get Rendang with standardized quality and taste. Rendang entrepreneurs who are members of UMKM (Small Entrepreneurs) need knowledge about spices and seasonings. The Cooperative in Padang City accommodates the rendang entrepreneur group. Community service activities have been carried out to increase the knowledge of Rendang entrepreneurs. The activity aims to socialize the importance of standardized spices and seasonings. Socialization has been carried out as a community service activity with the community development approach method. A presentation of the material by the speaker and a discussion was held with the participants. The speakers are food experts, plant cultivation, and rendang entrepreneurs whose businesses have developed. The socialization was held at the Truntum Padang Hotel. The results are that making a standardized rendang product requires quality spices and seasoning ingredients. The speaker's presentation informs Rendang entrepreneurs about quality ingredients for Rendang production. The essential ingredients of spices and suitable processing methods will produce quality seasoning products.